Hyperelastic and viscoelastic properties of recycled rubber material – experimental and fem characterization study - Juan S. Rodriguez-Piedrahita; Liseth A. Muñoz-Gutierrez; Ingrid E. Madera-Sierra; Diego D. Pérez-Ruiz; Orlando Cundumí-Sanchez (Polymer Testing)
Seismic hazards pose a significant threat to structures worldwide, with conventional rubber base isolators being cost-prohibitive for developing countries. This study investigates recycled rubber (RR) simulations as an alternative approach for seismic isolator testing and performance prediction, aiming to reduce the need for extensive experimental testing through numerical modeling. The methodology involved characterizing an RR mix through multiple deformation modes (uniaxial compression and tension, simple shear, creep, and relaxation). Using an iterative error reduction method that considered all modes simultaneously, the Bergström-Boyce model achieved an average R2 value of 0.92 for the RR matrix alone. The calibration process was then extended to an RR-textile reinforcement prototype using distinct coefficients for different deformation intervals. The model achieved average errors of −10.5 % in vertical stiffness, 5.2 % in horizontal stiffness, and 8.0 % in damping ratio when compared to experimental data, demonstrating its potential for predicting isolator behavior. This research contributes to the UN's Sustainable Development Goals by examining sustainable and resilient infrastructure solutions through the use of recycled materials in earthquake-resistant structures.